"Rules You Have to Know": International and Domestic Student Encounters with Institutional Habitus Through Group Work - Seithers, Laura; Amankulova, Zhuldyz; Johnstone, Christopher (Journal of International Students, 2021)
As more universities internationalize, interest in engagement between international and domestic students has increased. University initiatives to bring students together often adopt a deficit approach dependent on international students’ adjustment to the host culture, overlooking the need for engagement to be a two-way exchange and the role of the institution in this process. Focusing on academic group work as a salient site of cross-national interaction, this study draws on analysis of focus group data to explore how “institutional habitus” (Cornbleth, 2010; Reay et al., 2001), or unwritten rules, are enacted at a large U.S. university. Findings indicated that domestic students were better socialized to understand the habitus of the institution and tended to take charge in group work. In contrast, international students were seen as linguistically and academically deficient and were relegated to passive roles in a group. Important implications for practitioners and scholars of U.S. higher education are discussed.